The Effect of Students' Participation in the Youth Forum Training on the Level of the Second Five-Kick Soccer Players - Mohammed Abed, Ahmed; Noori Khazaal, Ali; Ali Mohammed, Jassim (International Journal of Psychosocial Rehabilitation, 2020)
Definition of the research included the definition and importance of introduction, touched on the importance of the game of football and the importance of PeCB use the delicate process in choosing players representing team Penta football Karkh Directorate, as well as to the role of youth forums in support of school sports to its student and training capacities of cadres, while the identified problem that there are scientific methods and process in the selection of elected elements Penta football in Karkh Directorate II but is supported on views